KAJIAN PEMBANGUNAN KABUPATEN ADMINISTRASI KEPULAUAN SERIBU BERBASIS KELAUTAN DAN PERIKANAN - Herie Saksono; Daniel R. Monintja; Soepanto Soemakaryo; Mulyono S. Baskoro (Buletin PSP, 2007)
Indonesia has 440 regencies/cities which 279 among them are the region that belong to sea/coastal based on fisheries. Most of their potential source is from marine resources both marine biological diversity or not. The aim of this research is a model for regency/city based on fisheries industry know the effect and as far as the effect’s some components which interact in the establisment. The research is held on Kabupaten Administrasi Kepulauan Seribu DKI Jakarta Province. The analysis and model development is done by Structural Equation Modelling (SEM). Based on the result of analysis is founded important several components that are reacted and correlated positive significantly in the developing of Kabupaten Administrasi Kepulauan Seribu such as between implementation of central government authority and regional government authority with the job fisheries also the establishment of job fisheries. This condition gives double effect of the goal of fisheries development and the highly society welfare on the Kabupaten Administrasi Kepulauan Seribu oriented by developing regency based on fisheries industry. Through this study, hope the government of Kabupaten Administrasi Kepulauan Seribu could review several development policies as soon as possible to be more oriented in using sea resource based on fisheries industry mainly on the area as conservations is synchronized and harmonized between regional development and regional function. Besides that fishery businessman in their establishment of fishery industry, can formulate the ideal model to develop their business planning with responsibility of implementation the function and care in using.